Local election campaign finance regimes in Canada: Toward a research agenda. (3rd April 2021) - Taylor, Zack; Vanhooren, Shanaya
Abstract: The regulation of election campaign donation, fundraising, expenditure, and advertising is an enduring object of study and reform. Compared to the federal and provincial levels, virtually no attention has been paid to Canadian municipal campaign finance regimes. This is surprising given the urban political economy literature's focus on business influence on local politics and policy and evidence of corruption in Canadian local government. We take stock of Canadian campaign finance rules for municipal elections in light of Canadian and American research findings, which reveals considerable interprovincial variation in their sophistication and stringency. We then propose a research agenda to investigate aspects of Canadian local campaign finance regimes. Sommaire: La réglementation des dons de campagne électorale, de la collecte de fonds, des dépenses et de la publicité constitue un objet tenace d'étude et de réforme. En comparaison aux paliers fédéral et provinciaux, les régimes canadiens de financement des campagnes municipales n'ont pratiquement reçu aucune attention. C'est un fait étonnant compte tenu que la littérature sur l'économie politique urbaine se focalise sur l'influence des entreprises dans la politique et les politiques locales et les preuves de corruption dans les administrations locales canadiennes. Nous faisons le point sur les règles de financement des campagnes électorales municipales au Canada à la lumière des résultats de recherches canadiennes et américaines, qui révèlent des variations interprovinciales considérables dans leur complexité et leur rigueur. Nous proposons ensuite un programme de recherche pour étudier les aspects des régimes canadiens de financement des campagnes électorales locales.